#TITLE_ALTERNATIVE# - SYAHRADZI (NIM : 13607066); Pembimbing : Dr. Ir. Bambang Kismono Hadi; Dr. Ir. Rais Zain, ARINI
Engine mounting is one of aircraft support structure which serves as a place of aircraft engine installation to other parts of the aircraft, such as fuselage and wings. Hence the importance of this engine mounting, it is necessary to design the engine mounting structure and analyze the strength of the engine mount structure that has been designed in order to produce a powerful engine mounting structure. This thesis research focused on the structure of MJK Fighter Aircraft’s engine mount. The design of the engine mounting structure is done by making a comparative study on similar aircraft and then adjusted to MJK Fighter Aircraft’s configuration. After the engine mounting structure is designed, the most critical loading conditions are applied to the structure. In this research, the critical loads are the maximum thrust produced by the engine and the maximum load factor, n=+9. Analysis using finite element method is then performed to obtain the stress characteristic and to evaluate the strength of the structure, whether it is capable of withstanding the critical loads given or not. From five iterations that have been performed, the results showed that there are four engine mount structure configurations that produce maximum stresses lower than the yield strength of the material. This means that the four engine mounting structures are capable in withstanding the critical loads. Then from the four configurations, it can be determined which structure is the most efficient by determining the safety factor for each engine mounting structure configuration.